Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1097/01.asn.0000070154.00058.b4
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Public Health Approach to Address the Burden of Renal Disease in Singapore

Abstract: Abstract. With the epidemic rise of ESRD in multiple regions of the world, there is an urgent need to implement programs to address this increasing burden of kidney disease. We illustrate a public health approach using the program of the National Kidney Foundation of Singapore that incorporates stepwise primary, secondary, and tertiary strategies for prevention. Components of the program include an aggressive public education program, routine surveillance for kidney disease and associated chronic diseases, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…As evidenced by a substudy of the screening program, 73.7% of the diabetic patients studied had poor glycemic control as defined by a hemoglobin A1c of 7.0% or greater. In addition, 88.2% were found to have an elevated blood pressure, and 47% of the screened diabetics had incipient diabetic nephropathy as defined by the presence of microalbuminuria (20). These observations supported the design of a secondary prevention strategy, which has 2 main components.…”
Section: Early Intervention and Disease Management Programmentioning
confidence: 67%
See 3 more Smart Citations
“…As evidenced by a substudy of the screening program, 73.7% of the diabetic patients studied had poor glycemic control as defined by a hemoglobin A1c of 7.0% or greater. In addition, 88.2% were found to have an elevated blood pressure, and 47% of the screened diabetics had incipient diabetic nephropathy as defined by the presence of microalbuminuria (20). These observations supported the design of a secondary prevention strategy, which has 2 main components.…”
Section: Early Intervention and Disease Management Programmentioning
confidence: 67%
“…In Singapore, several factors influenced the development of a chronic kidney disease screening program (19,20). The rising annual incidence of ESRD in Singapore (1), its profound impact on morbidity and mortality, and the country's ethnic composition, which may suggest an increased predisposition to kidney disease such as IgA nephropathy (21), among others, led to the development of the Prevention Program of the NKF Singapore.…”
Section: Epidemiologic Basis For Screening For Chronic Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Focus on IEC measures, intervention programs, facility provisioning and expansion along with extensive research has been identified as the ultimate gainful resource for the successful public health program in Singapore. 3 It surely facilitates collaborative, correctional and coordinated inputs by all possible stakeholders.…”
Section: Introductionmentioning
confidence: 99%